Karakteristik Bangunan Rumah Tinggal Di Pesisir Kabupaten Majene Terhadap Gempa - Yusman Yusman (Departemen Teknik Kelautan Universitas Hasanuddin, 2021)
The meeting of the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate makes Indonesia's geological condition unstable so that it is prone to earthquakes. Majene Regency is an earthquake-prone area, so earthquake-resistant buildings are recommended. The purpose of this study was to identify and classify the number of houses affected by the earthquake and the causes of the high level of damage. The methods used are survey and interview methods. The survey process was carried out by observing residents' houses and classifying the level of damage based on technical instructions issued by the 2019 Ministry of PUPR Ministry of PUPR's Research and Development Center for Building Materials & Structures. From the survey results, there were 1,713 heavily damaged houses, 1,060 moderately damaged and 1,107 lightly damaged houses. From the results of surveys and interviews, it was found that the condition of the structure of the house in general is not in accordance with the guidelines for housing and settlement development by the Research and Development Center Team for Building Materials & Structures of the Ministry of PUPR. 2016 which does not have a sloof, ring beam or column, resulting in a higher percentage of house damage